The differences between the quality of life of malays and nonmalays breast cancer survivors women from a Teaching Hospital,Kuala Lumpur: a qualitative study - Redhwan AA; Idris MN; Fuad I; Robert C; Hairol O (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : The purpose of this study is to explore the differences of quality of life (QOL) of Malay and non-Malay breast cancer survivors using qualitative method. Methods : Data was collected using in-depth face to face interview. List of the patients were obtained from Oncology & Surgery Departments and contact numbers were obtained from the medical record. The interviews were conducted either in their home or in the hospital after the appointment has been made. Results : The majority of the Malays were unable to fulfill the needs of their families. However, the non-Malays were able to fulfill the needs of their families. The majority were satisfied with social interaction and the relationships with their families and friends. In terms of feelings, most survivors felt sad, angry and sometimes they feel like they were going to die early. However the majority coped well with their illness. Regarding sleep, all Malays did not have any sleeping problems, but most of the non-Malays reported serious problems. All survivors were worried about the other female members of the family of getting the same illness. Most survivors did not have any problems with altered body image. Conclusion : Malays did not have any sleeping problems, but most of the non-Malays reported serious problems. However, the majority of survivors coped well with their illnesses.